AUTOMATION OF PRODUCTION PROCESSES AND DATA PROCESSING METHODS IN TOURISM - Nazarov, Husanbek (University Research Base, 2025)
The rapid advancement of automation technologies and data processing methods is significantly transforming the tourism industry. This study explores the impact of robotic process automation (RPA), artificial intelligence (AI), and big data analytics on operational efficiency, cost reduction, and customer satisfaction within tourism enterprises. Quantitative data from 150 tourism businesses across four countries and qualitative insights from 20 industry stakeholders reveal that businesses implementing automation technologies experience a 35% increase in process speed and a 25% reduction in operational costs. However, the findings also highlight ethical concerns, particularly regarding job displacement and the loss of human-centered services. Furthermore, the integration of big data analytics has improved decision-making and service personalization, though challenges related to data privacy remain. The study concludes that while automation presents substantial operational benefits, businesses must adopt a balanced approach that incorporates workforce retraining, data security measures, and sustainable automation technologies to mitigate environmental impacts and ensure long-term industry growth.